2002
DOI: 10.1159/000049348
|View full text |Cite
|
Sign up to set email alerts
|

A Randomised Controlled Clinical Trial on the Additional Effect of Hypnosis in a Comprehensive Treatment Programme for In-Patients with Conversion Disorder of the Motor Type

Abstract: Background: The primary aim of this study was threefold: (1) to examine the additional effects of hypnosis aimed at symptom reduction, using symptom-oriented and expression- and insight-oriented techniques in a comprehensive clinical treatment programme for in-patients with a persistent conversion disorder of the motor type; (2) to assess whether the level of hypnotisability was predictive of treatment outcome, and (3) to explore the efficacy of the total clinical treatment programme. Methods: The study popula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
73
0
17

Year Published

2005
2005
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(90 citation statements)
references
References 29 publications
0
73
0
17
Order By: Relevance
“…An additional study has shown that symptom reduction was observed independently of the treatment condition (i.e. comprehensive program vs hypnosis added to a comprehensive program) [41]. Later, significant treatment results were reported for hypnosis-based therapy in patients with conversion disorders as compared to a no-treatment group [42].…”
Section: Hypnosis As a Substitute For Hysteria?mentioning
confidence: 99%
“…An additional study has shown that symptom reduction was observed independently of the treatment condition (i.e. comprehensive program vs hypnosis added to a comprehensive program) [41]. Later, significant treatment results were reported for hypnosis-based therapy in patients with conversion disorders as compared to a no-treatment group [42].…”
Section: Hypnosis As a Substitute For Hysteria?mentioning
confidence: 99%
“…Moene et al [41] conducted a RCT in a group of 45 patients with conversion disorder (motor type) or somatization disorder (with motor conversion symptoms) evaluating the efficacy of adding hypnosis to a standard inpatient treatment. Patients in both treatment (standard inpatient program+hypnosis) and control (only inpatient program) groups followed a group therapy program with the aim of increasing problem-solving skills (including group psychotherapy, social skills training, formulation and evaluation of treatment goals, creative therapy, and sports, physiotherapy, and individual exercise sessions).…”
Section: Hypnosismentioning
confidence: 99%
“…Moene et al [41] reported on the usefulness of the addition of hypnosis to an inpatient program (see above). Although the hypnosis treatment did not provide additional benefit to the inpatient program, the treatment program itself did lead to improvement in symptoms in the majority of patients.…”
Section: Inpatient Multi-disciplinary Therapymentioning
confidence: 99%
“…Results from two trials of hypnosis have been contradictory. 26,27 Preliminary findings from studies with small sample sizes suggest that antidepressant medication, 28 behavioural therapy, 29 paradoxical intention 30 and transcranial magnetic stimulation 31 may be effective, but these results need to be replicated. From a theoretical standpoint, the data on transcranial magnetic stimulation are intriguing.…”
Section: Which Treatments Are Effective?mentioning
confidence: 99%